Relationship of the White Coat Effect with Endpoints and Several Prognostic Indicators in Hypertensive Patients Treated with Regular Antihypertensive Therapy - G. F. Andreeva; M. I. Smirnova; V. M. Gorbunov; A. S. Kurekhyan; Y. N. Koshelyaevskaya (Рациональная фармакотерапия в кардиологии, 2023)
Aim of the study was to evaluate in a prospective cohort study the relationship between the severity of the white coat effect (WHE) in patients with hypertension, who treated with regular antihypertensive therapy, and the composite endpoint, several prognostic indicators, in a routine clinical practice.Material and Methods. We analyzed the data of a prospective cohort study, which included 125 patients with hypertension who received regular antihypertensive therapy. The study consisted of three visits (baseline, 6 and 12 months) and an outcome data collection period (30.1±7.6 months of follow-up after the third visit). This study included three visits every 3 months: 1 visit – screening, ambulatory blood pressure monitoring (ABPM) session, Echo; 2 – assessment of the patient’s status and the therapy effectiveness; 3- assessment of the patient’s status, ABPM session, Echo (the total number of ABPM was 239, Echo - 240). The primary composite endpoint included death for any reason angina pectoris, transient ischemic attack, development of chronic heart failure, arterial revascularization, frequent ventricular extrasystoles, atrial fibrillation, secondary - deterioration of the cardiovascular diseases course and tertiary endpoint – deterioration of the arterial hypertension, concomitant diseases course.Results. The study involved 125 patients: 28 men (22%), 97 women (78%), mean age was 62.6±0.8 years, duration of hypertension 11.6±0.8 years, height 163.6±0.7 cm, body weight 83.1±1.4 kg. The baseline mean daytime systolic BP (SBP) was 125.1±9.8 and diastolic (DBP) – 76.1±7.0 mm Hg, age was 62.8±9.0 years, the WCE level for SBP was 16.5±1.4, for DBP 10.9±0.7 mm Hg. We identified a positive correlation between tertiary composite endpoint data and WCE: for systolic WCE (SWCE) (F = 4.7, p<0.031). We found correlations between WCE and Echo parameters: 1) SWCE level had with LVMI (r = 0.16. p<0.017); 2) diastolic WCE (DWCE) had negative relationship with LV contractility parameters.Conclusions. Thus, only systolic WCE level had correlation with composite endpoint data and LVMI. DWCE level had negative associations with echocardiography LV contractility parameters.